SMEs’ investment determinants: empirical evidence using quantile approach - Nunes, Paulo Maçãs; Mendes, Sílvia; Serrasqueiro, Zélia (Journal of Business Economics and Management, 2012)
This paper makes an important contribution to the literature on SMEs, namely investigating whether the relationships between determinants and investment are dependent on the level of investment. Based on a sample of Portuguese SMEs, using two-step estimation method, firstly using probit regression and secondly using quantile regressions, we find significant non-linearities in relationships formed between determinants and investment over the distribution of investment. In particular, we find that: 1) sales, age and growth opportunities are restrictive determinants of investment for low levels of investment, but positive determinants of investment for high levels of investment; 2) debt and the interest rate are restrictive determinants of investment but only for low and intermediate levels of investment; 3) cash flow is a positive determinant of investment, but is more important for investment regarding low levels of investment; 4) GNP is a positive determinant of investment, but only for high levels of investment; and 5) investment in the previous period is a positive determinant of investment in the present period, but only for intermediate and high levels of investment. The relevance of the various theories explaining firm investment depends on SMEs’ level of investment.